ANALISIS KEBIJAKAN PENGEMBANGAN BERBASIS KEBERLANJUTAN KABUPATEN KEPULAUAN MERANTI PROVINSI RIAU - Hazmi Arief; Ulfa Rizki Pradini (Indonesian Journal of Agricultural Economics, 2019)
The purpose of this study was to analyze the policy of sustainability-based development in Meranti Islands Regency by looking at the real conditions of coastal resources which consist of ecological, economic, social and technological dimensions. Indicators of sustainable development will not be separated from economic, ecological / environmental, social, political and cultural aspects. The method used in this study was the survey method. The population in this study were coastal communities in the Meranti Islands. To obtain and analyze the policy of sustainable development in the coastal area of Meranti Islands, it was analyzed using the Analysis Hierarchy Process (AHP) method. The arrangement of AHP's hierarchy of decision making with actors is the Regional Government, Fisheries and Marine Services, Bappeda, Environmental Agency, Food Security Agency, Plantation Service, Food Crop Agriculture Service and Social Welfare Service. The results of policy analysis through AHP, that the priority sectors that need to be developed in the context of sustainable development in the coastal areas of the Meranti Islands Regency are fisheries and plantation sectors with a score of 0.632. The existing characteristics and conditions of coastal communities in Meranti Islands Regency are farmers, farmers and fishermen communities, fishing communities and urban / industrial communities.